"الحملات الصليبية وتأثيراتها على الوضع السياسي والاقتصادي في المشرق الإسلامي" (Comprehensive Journal of Science, 2025)
The aim of the research was to analyze the impact of the Crusades on political systems in the Islamic East, monitor the economic effects of the Crusades on trade, agriculture, and industry in the Islamic world, and highlight the social impacts resulting from the Crusades on Islamic societies. The research also aimed to identify the political, economic, and social